The Strategic Role of Women's Leadership in Indonesia - Hera Hayuda Pradani; Ranaa Andini Wirawan; Achmad Ryan Satria; Vina Aprilia Hidayat (Journal of World Science, 2025)
Women’s leadership in Indonesia is increasingly demonstrating its strategic role across various sectors, from business to government. This study examines the contributions of female leadership to organizational sustainability, performance effectiveness, innovation, and cultural transformation. Despite facing structural challenges such as gender stereotypes, limited support, and patriarchal systems, female leaders have proven capable of fostering inclusive, collaborative, and ethical work environments. With leadership styles rooted in empathy, participation, and communication, women leaders promote work-life balance, inclusive decision-making, and the development of adaptive organizational cultures. The study concludes that empowering and developing women’s leadership is a strategic necessity that must be supported by organizational policies, leadership development programs, and supportive work ecosystems to enhance diversity and organizational competitiveness in the global era.